The diffusion of ferrocyanide and ferricyanide ions in aqueous solutions of potassium hydroxide - Arvia, Alejandro Jorge (1967)
The diffusion of ferro- and ferricyanide ions in potassium hydroxide solutions has been studied with the rotating disk electrode between 24 and 50°C. The quotient Dη/T was satisfactorily constant and temperature-independent. A comparison with previous results obtained for solutions containing sodium hydroxide and potassium chloride as supporting electrolytes is made.